2014
DOI: 10.1155/2014/423174
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 20-Gene Expression-Based Risk Score as a Predictor of Clinical Outcome in Chronic Lymphocytic Leukemia Patients

Abstract: Despite the improvement in treatment options, chronic lymphocytic leukemia (CLL) remains an incurable disease and patients show a heterogeneous clinical course requiring therapy for many of them. In the current work, we have built a 20-gene expression (GE)-based risk score predictive for patients overall survival and improving risk classification using microarray gene expression data. GE-based risk score allowed identifying a high-risk group associated with a significant shorter overall survival (OS) and time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…However, single molecular biomarkers often fail to predict the survival of gastric cancer due to their heterogeneity, while transcriptome-based classification includes redundant information. However, the multiple molecular biomarker-based model has been proven to be robust across datasets and has been implemented in cancer ( Bou Samra et al, 2014 ; Chang et al, 2014 ; Kim et al, 2014 ; Salazar et al, 2011 ; Wu et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, single molecular biomarkers often fail to predict the survival of gastric cancer due to their heterogeneity, while transcriptome-based classification includes redundant information. However, the multiple molecular biomarker-based model has been proven to be robust across datasets and has been implemented in cancer ( Bou Samra et al, 2014 ; Chang et al, 2014 ; Kim et al, 2014 ; Salazar et al, 2011 ; Wu et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical prognostic effect of single molecular biomarkers varies across datasets; whereas a multiple gene expression-based staging method is robust across datasets (7)(8)(9)(10). In the present study, a transcriptome-based risk score for the prediction of survival in patients with ER+ breast cancer treated with tamoxifen was developed using the Cox multivariate regression model.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we observed that these three genes were highly associated with survival using a completely different methodological approach and the same cohort (GSE22762). Conversely, Bou et al [ 50 ] proposed a risk score combining with NRIP1 and TCF7 expression to identify high-risk patients. Therefore, the involvement of these genes in disease prognosis is significant.…”
Section: Discussionmentioning
confidence: 99%